Evaluasi Kualitas Layanan Sistem Keuangan Desa Menggunakan Webqual 4.0 - Febriyanti Panjaitan; Susan Dian Purnamasari; Candra Buana (Journal of Information Technology Ampera, 2022)
The application of this information technology has been carried out in government agencies. BPKP together with the Ministry of Home Affairs developed the Village Financial System Application. One that has implemented this application is a village in Gunung Megang District, Muara Enim Regency. This system makes it easier for the village government to make village budgets, bookkeeping and financial reporting to the central government, in order to oversee the transparency of village financial reporting and the use of policies in the use of village budgets. To see the quality of this application service to users, namely Staff perangkat desa, it is necessary to evaluate user satisfaction. This research activity was carried out using the Webqual 4.0 method because this method has been used by several researchers and they concluded that this method provides results that are always valid with a description of which variables have an effect on user satisfaction. This method has 4 variables, namely usability, information quality, service interaction and Overall Impression. Based on the evaluation results with 35 respondents and 15 questions using validity testing, the correlation value for each question item is greater than r table, while in reliability testing Cronbach's alpha is 0.971 and in testing based on the Likert scale range it is stated that the level of satisfaction of SISKEUDES users is in good category